2004
DOI: 10.1111/j.1365-4632.2004.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG class antibodies from psoriasis patients recognize the 60‐KDa heat‐shock protein of Streptococcus pyogenes

Abstract: Results suggest that a high response to the HSP60Sp could be associated with the chronic form of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In psoriasis, bacterial infection seems to play an important role in the etiology of the disease. Several products of Gram-positive bacteria, such as M protein, 28,29 superantigens, 30,31 and heat shock proteins, 32 have been associated with the humoral and cellular immune response of psoriatic patients. Recently, Baker et al 33 have reportedthat, in biopsiesfrompatientswithpsoriasis, there are macrophages containing PGN and T-helper-1 (Th1) cells, which respond specifically to PGN from S. pyogenes.…”
Section: Discussionmentioning
confidence: 99%
“…In psoriasis, bacterial infection seems to play an important role in the etiology of the disease. Several products of Gram-positive bacteria, such as M protein, 28,29 superantigens, 30,31 and heat shock proteins, 32 have been associated with the humoral and cellular immune response of psoriatic patients. Recently, Baker et al 33 have reportedthat, in biopsiesfrompatientswithpsoriasis, there are macrophages containing PGN and T-helper-1 (Th1) cells, which respond specifically to PGN from S. pyogenes.…”
Section: Discussionmentioning
confidence: 99%
“…They are highly immunogenic proteins, and it is suggested that they can develop autoimmunity after infection because of the sequence homology between bacteria and human 6 . In one study, Cancino‐Diaz et al 7 found that the serum of patients with psoriasis contained a higher level of antibody to the HSP60 of Streptococcus pyogenes than did the control group. Rambukkana et al 8 showed that the majority of their patients with chronic plaque‐type psoriasis showed strong antibody activity to the recombinant mycobacterium HSP65 7 .…”
mentioning
confidence: 99%
“…In one study, Cancino‐Diaz et al 7 found that the serum of patients with psoriasis contained a higher level of antibody to the HSP60 of Streptococcus pyogenes than did the control group. Rambukkana et al 8 showed that the majority of their patients with chronic plaque‐type psoriasis showed strong antibody activity to the recombinant mycobacterium HSP65 7 . HSPs are known to be recognized by γδ T‐cell receptors (TCR‐γδ) and Toll‐like receptors (TLRs) 2 and 4 and consequently alert innate and adaptive immune systems 9,10,11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lesion-specific reactivity to HSP subgroups was demonstrated. Guttate type is associated with 14-kDA HSP, 65- and 71-kDA HSP are associated with the plaque form of the disease [13]. De Strooper et al [14] showed in vitro hyper-reactivity of the 68-kDa antigen to the psoriatic keratinocytes.…”
Section: Discussionmentioning
confidence: 99%